Plasma Estradiol concentrations during prepartum vaginal prolapse in buffaloes - KUMAR, R SURESH; VERMA, H K; UMAPATHI, L; GANDOTRA, V K; KASRIJA, RAJESH (The Indian Journal of Animal Sciences, 2011)
Blood samples were collected from 15 buffaloes having prepartum prolapse of vagina before (Group 1) and after treatment (Group 2) and from five normal pregnant (Group 3) buffaloes to study the estrogen as a possible cause of prolapse. In Group 3, the estradiol concentration remained almost constant during sixth to nine month of gestation with a gradual increase and during nine and tenth month, it increased steadily and reached a peak value of about 515 pg/ ml on the day of calving. There was a significant variation of estradiol before and after treatment with the corresponding stage of normal gestation during 6–8 months, 8–10 months and above 10 months of gestation. It suggests the role of estrogen as a cause of prepartum vaginal prolapse.